A multimodal study of the legitimization of violence in Rumiyah / Nazri Mohd Noor - Nazri , Mohd Noor (2020)
This study explored the process of legitimization of violence in Rumiyah magazine produced by al-Hayat Media Center (ISIS). It employs a multimodal approach consists of van Leeuwen (2008) legitimization strategies and Kress and van Leeuwen (2006) visual social semiotics to analyse texts and semiotic resources found in the selected articles. The qualitative method used is an inductive thematic analysis which reveals several thematic categorizations, i.e., (1) the impersonalisation of ‘others’, (2) the legitimization of jihad value, and (3) the (de)legitimization of ‘fasiq’ scholars. The analysis conducted highlights the recurring use of legitimation strategies and visual social semiotic metafunctions to justify violence in the Rumiyah magazine. The overall analysis indicates a complex interaction between the discursive and semiotics aspects of the study that are governed by ISIS’s ideological goals. Keywords: ISIS, discursive legitimization, social semiotics, terrorism, Rumiyah